Trading Days, Systematic Risk, and Daily Standard Deviation in LQ-45 Stocks - Yana Hendayana; Daniel Nababan; Ivan Gumilar Sambas Putra (Universitas Kristen Maranatha, 2023)
This study aims to assess the impact of trading days and systematic risk on the daily standard deviation of stocks in LQ-45 companies. This study includes a sample of 45 companies listed on the LQ-45 index of the Indonesia Stock Exchange. This study uses purposive sampling as the participant selection method. Hypotheses were tested using multiple linear regression analysis on SPSS version 26, with secondary data obtained from the Indonesia Stock Exchange. This study has identified a significant relationship between trading days and systematic risk, which in turn affects the standard deviation of stocks. The purpose of this study is to investigate the impact of trading days and systematic risk on the daily standard deviation of stocks owned by companies listed in the LQ-45 index. Based on the results, it is concluded that trading days have an influence on the daily standard deviation of stocks, with Friday showing a significant impact. There is a positive correlation between the level of systematic risk and the magnitude of a stock's daily standard deviation. Keywords: Trading Days, Systematic Risk, and Annual Standard Deviation